Reading: How Readers Beget Imagining - Trasmundi, Sarah Bro; Cowley, Stephen J. (Frontiers in Psychology, 2020)
We trace reading to an embodied synthetic process that drives the rapid scales of imagining. As sensorimotor engagement with written artefacts permeates experience, it sharpens the sensibility that brings forth understanding. We thus trace material engagement with written artefacts to fine control over saccadic eye movements and voicing that draws on human s or what the Greeks knew as aisthesis. In reading, we identify aisthesis in how pre-reflective judgements punctuate the flow of engagement with written documents. While the study of reading often begins with ‘texts’, we start with how written artefacts are put to use. We use cognitive ethnography to trace reading to how fine multi-scalar coordination enables readers to engage with written artefacts such as books. Our ethnography of reading provides descriptions of how readers use sensorimotor activity to integrate understanding with saccading and actual or imagined vocalisation in ways that show how reading connects sensorimotor schemata with highly skilled use of written artefacts. By pursuing the power of rapid multi-scalar dynamics, we complement views of reading as slow-scale subjective experience. Rather than focus on interaction between a reader and an imagined author, we turn to coordinating with an affordance-rich environment. Human pre-reflective judgements demonstrably use collective experience with written signs. In fine-grained analysis of authentic data, we therefore track kinaesthetic experience to how a child’s vocalisations beget understanding and, at once, imagining. These observations show how engagement brings life to written signs by connecting other peoples’ pasts with use of gaze, gesture, voice and touch. While describing saccades and bursts of vocalising, we reach beyond analogies with interaction and, in so doing, the multi-scalar approach takes enactive-ecological work beyond the slow interactional and social scales or reported experience. Imagining arises as readers use multi-scalar happenings to bind the anticipated, the seen and collective aspects of experience.